2004
DOI: 10.1182/blood-2003-12-4383
|View full text |Cite
|
Sign up to set email alerts
|

The t-PA -7351C>T enhancer polymorphism decreases Sp1 and Sp3 protein binding affinity and transcriptional responsiveness to retinoic acid

Abstract: We have previously identified a common polymorphism at the tissue-type plasminogen activator (t-PA) locus (؊7351C>T), located within a GC-box in the retinoic acid (RA) and steroid hormone responsive t-PA enhancer. The aim of the present study was to functionally characterize this t-PA variant. Electrophoretic mobility shift assays (EMSAs) using crude nuclear extracts from human endothelial, HeLa, and NT2 neuronal cells revealed a 10-fold greater protein binding affinity to the wild-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 39 publications
4
36
0
Order By: Relevance
“…Several in vitro studies have demonstrated this region to contain a binding site for the Sp1 transcription factor. [32][33][34] The C to T substitution at rs2020918 has been shown reduce the affinity of Sp1 to this site, suggesting a mechanism by which rs2020918 is associated with lower tPA transcription. 31,34 Our PLAT association results for the combined CVD end point replicate 2 previous studies in small samples of an association of rs2020918 with MI or stroke.…”
Section: Tissue Plasminogen Activatormentioning
confidence: 99%
See 1 more Smart Citation
“…Several in vitro studies have demonstrated this region to contain a binding site for the Sp1 transcription factor. [32][33][34] The C to T substitution at rs2020918 has been shown reduce the affinity of Sp1 to this site, suggesting a mechanism by which rs2020918 is associated with lower tPA transcription. 31,34 Our PLAT association results for the combined CVD end point replicate 2 previous studies in small samples of an association of rs2020918 with MI or stroke.…”
Section: Tissue Plasminogen Activatormentioning
confidence: 99%
“…[32][33][34] The C to T substitution at rs2020918 has been shown reduce the affinity of Sp1 to this site, suggesting a mechanism by which rs2020918 is associated with lower tPA transcription. 31,34 Our PLAT association results for the combined CVD end point replicate 2 previous studies in small samples of an association of rs2020918 with MI or stroke. In a populationbased nested case-control study (61 MI cases and 120 controls), individuals bearing the minor T allele had a significant 2.7-fold increased odds of MI compared with the CC genotype, a risk estimate similar to our finding.…”
Section: Tissue Plasminogen Activatormentioning
confidence: 99%
“…5 The mutant T allele confers a reduced transcriptional activity in vitro, and in vivo this allele is associated with reduced tPA release rates as well as increased risk of myocardial infarction (MI). [5][6][7] A recent study also reported an increased risk of ischemic stroke for the TT genotype. 8 The main inhibitor of tPA in plasma is plasminogen activator inhibitor type 1 (PAI-1), and experimental studies demonstrate that PAI-1 delays clot lysis.…”
mentioning
confidence: 99%
“…−7351 C/T single nucleotide polymorphism of the gene encoding t-PA (rs63020761) is located within the enhancer region and the substitution of cytosine for thymine at position −7351 reduces the Sp1/Sp3 binding affinity resulting in the inhibition of DNA transcription [12]. This polymorphism was found to be strongly correlated with reduced endothelial t-PA release [13] and associated with the occurrence of myocardial infarction and stroke [14, 15].…”
Section: Introductionmentioning
confidence: 99%